2021
DOI: 10.1002/mgg3.1752
|View full text |Cite
|
Sign up to set email alerts
|

The associations of CNR1 SNPs and haplotypes with vulnerability and treatment response phenotypes in Han Chinese with major depressive disorder: A case–control association study

Abstract: Background Understanding how genetic polymorphisms are associated with the pathophysiology of major depressive disorder (MDD) may aid in diagnosis and the development of personalized treatment strategies. CNR1 is the gene coding Cannabinoid type 1 receptor which is highly involved in emotional processing and in regulating neurotransmitter releases. We aimed to investigate the associations of CNR1 single‐nucleotide polymorphisms (SNPs) with MDD susceptibility and treatment response. Methods The study reported d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The CUX2 gene exhibited the greatest positive correlation and high expression in the primary sensory and visual cortex. As a key component of the endocannabinoid system, the CNR1 contributed to the support of the molecular architecture of processing reward and perception of certain basic emotions, and was even regarded as a promising genetic predictor for diagnosis of MDD and treatment response to antidepressants (Icick et al, 2015 ; Yang, Nolte, et al, 2021 ; Yao et al, 2018 ). For example, previous research has shown that variations in CNR1 modulated the striatal response to emotional faces (Anderson, Collins, Chin, et al, 2020 ; Mecca et al, 2021 ; Tsuboi et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The CUX2 gene exhibited the greatest positive correlation and high expression in the primary sensory and visual cortex. As a key component of the endocannabinoid system, the CNR1 contributed to the support of the molecular architecture of processing reward and perception of certain basic emotions, and was even regarded as a promising genetic predictor for diagnosis of MDD and treatment response to antidepressants (Icick et al, 2015 ; Yang, Nolte, et al, 2021 ; Yao et al, 2018 ). For example, previous research has shown that variations in CNR1 modulated the striatal response to emotional faces (Anderson, Collins, Chin, et al, 2020 ; Mecca et al, 2021 ; Tsuboi et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Longer AAT repeat expansions can produce a Z-shaped DNA conformation, thereby potentially downregulating gene transcription [ 111 ]. In this context, the CNR1 SNPs rs6454674 and rs806367 have been indicated to increase vulnerability to major depressive disorder and resistance to antidepressant treatment [ 114 ]. However, a recent meta-analysis did not reveal an association between CNR1 rs1049353 or AAT repeat polymorphism with depression risk [ 115 ].…”
Section: Genetic Factors Associated With Depression In Idiopathic Par...mentioning
confidence: 99%
“…The haplotype comprising rs806366, rs806367, rs806368, and rs806370 SNPs was associated with the vulnerability to develop MDD and resistance to antidepressant therapy. They hypothesized that CNR1 genetic polymorphisms are associated with a higher probability of developing MDD and within depressed patients with a higher likelihood of resistance to antidepressant treatment [234] (Table 6).…”
Section: Clinical Studiesmentioning
confidence: 99%
“…In WT mice, LY2828360 blocked morphine-induced reward in a CPP paradigm, whereas morphine-induced reward was absent in CB2r KO mice. LY2828360 partially attenuated naloxone-precipitated opioid withdrawal in morphine-dependent WT mice, whereas this withdrawal was markedly exacerbated in CB2r KO mice [474] Animals Maternally deprived adolescent rats Maternally deprived adolescent rats exhibited ↑ AEA in the NAcc, the Cpu nucleus, and the mesencephalon Maternally deprived adult rats, showed ↑ AEA and 2-AG in the NAcc, and ↑ 2-AG in the CPu nucleus [177,273,275] [193,195,196,230,231,233,269,271,271, 276,375,376,396,397,430,434] [134] [234,271,396] [234] [234,269,270,375,396,430,434,451,460,470] [396]…”
Section: Authorsmentioning
confidence: 99%